Analysis of factors which define time losses in traffic flow - Bura, Romana; Davosyr, Vladyslav (Видавництво Львівської політехніки, 2017)
Reviewed geometric and planning road network parameters which impact on delays of movement in traffic flows, and also organizational questions, connected with them. Analyzed factors, which reduce vehicular speeds and encourages traffic jams generation.
Keywords: time losses; traffic delays; road network; speed of movement; traffic flow